A Comparative Study of Routine Microscopic Examination of Urine in Microbiology Laboratories at Primary and Secondary Level Before and After Implementation of Standard Operating Procedure (SOP) (Journal of Dhaka Medical College, 2017)
Context : Laboratory services have become an integral and inseparable component of modern medicine and public health. The use of standard operating procedure (SOP) in laboratory testing is one of the most crucial factor in achieving the quality. This cross sectional study was done to assess the quality of routine microscopic examination of urine of a microbiology laboratory at primary level and one microbiology laboratory at secondary level by evaluating the test results before SOP and re evaluating the test results after implementing SOP to see if there was any improvement in quality of those tests.Material and Methods: A cross sectional, descriptive type of study was conducted in Narsingdi Sador Hospital as secondary level microbiology laboratory and Polash Upzilla Health Complex as primary level microbiology laboratory. The study was performed on clinically suspected patients of urinary tract infection (UTI) attending at the primary and secondary level laboratory for microscopic examination of urine. Clinically suspected cases of UTI who had taken any anti microbial treatment in the past 48 hours were excluded from the study. 60 urine samples were collected from each level before implementing SOP and 30 urine samples were collected from each level and tested after following SOP.Result : In routine microscopic examination of urine at primary and secondary level, before SOP, regarding significant number of Pus cells discrepancy was found in 21.67% cases at primary level and 18.33% cases at secondary level. After implementing SOP, discrepancy in the result was reduced to 10% from 21.67% at primary level and 0% from 18.33% at secondary level. This difference in results was statistically significant (p< 0.05).Conclusion: Implementing SOP and after practicing appropriate and standard techniques for collection and examination of urine at primary and secondary level, discrepancy in the results of routine microscopic examination of urine between investigator and Medical Officer (MOPathology) was reduced and overall quality of tests were improved.J Dhaka Medical College, Vol. 25, No.2, October, 2016, Page 87-93